Do flexible pollen foraging habits of Xylocopa frontalis (Apidae, Xylocopini) contribute to nest management in passion fruit crops?. Issue 5 (20th October 2017) - Junqueira, Camila Nonato; Rabelo, Laíce Souza; Bastos, Esther Margarida Alves Ferreira; Augusto, Solange Cristina
Abstract : Xylocopa bees provide efficient pollination services for yellow passion fruit orchards. Passion fruit is solely a nectar source for pollinators, and the use of pollen sources from the surroundings of crop areas is essential to sustain these pollinator populations. This study aimed to assess the food niche breadth of Xylocopa frontalis in the use of pollen sources in a breeding area and in two yellow passion fruit crops. We evaluated larval food samples from nests maintained in the breeding area and after their transference to crop areas. Based on pollen analysis, we verified differences in the food niche breadth and a shift in pollen sources among the study areas. In addition, although X. frontalis can be considered a plastic species regarding pollen sources, we observed that they concentrate foraging activities on few pollen sources, considering both cells and the areas studied. Information regarding pollen foraging habits performed by X. frontalis can contribute to the design more appropriate nest management strategies and maintain its populations in passion fruit crops in the long-term.